Coated lithium-rich lithium supplement agent material, preparation method and application thereof, and lithium ion battery

By introducing a carbon composite lithium-rich layer on the surface of Li2NiO2, the problem of poor stability of Li2NiO2 in humid air is solved, and the high air stability and lithium-enhancing capacity of the coated lithium-enriched lithium-enhancing agent material are achieved.

CN119852403AActive Publication Date: 2025-04-18STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411900735.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

In the prior art, Li2NiO2 has poor structural stability in humid air, resulting in the precipitation of LiO and Li2CO3, affecting the air stability and specific capacity of lithium supplement agents.

Method used

By introducing a carbon-composite lithium-rich layer, including Li2CO3, Li2C2O4 or Li2C4O4, the content and mass ratio of carbon elements is controlled within the range of 100:1-5:0.1-2.5, and a clad lithium-rich lithium-enriched agent material is prepared.

Benefits of technology

This material has excellent air stability and lithium supplement capacity. Through the synergistic effect of the carbon composite layer, the stability and lithium supplement effect of Li2NiO2 are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852403A_ABST
    Figure CN119852403A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a coated lithium-rich lithium supplement agent material, a preparation method and application thereof, and a lithium ion battery. The material comprises a base body and a coating layer coating the surface of the base body, the matrix is prepared from Li2NiO2; the coating layer comprises a carbon composite lithium-rich layer; the lithium-rich layer is selected from at least one of Li2CO3 (lithium carbonate), Li2C2O4 (lithium carbonate) and Li2C4O4 (lithium carbonate); the mass ratio of the content of carbon elements in the Li2NiO2 to the content of carbon elements in the lithium-rich layer to the content of carbon elements in the coating layer is 100: (1-5): (0.1-2.5); the average particle diameter of the coated lithium-rich lithium supplement agent material is 12-18 [mu] m. The coated lithium-rich lithium supplement agent material provided by the invention has excellent air stability and lithium supplement capacity, and is simple in preparation process, high in repeatability and easy to popularize on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a coated lithium-rich lithium supplement material, a preparation method and application thereof, and a lithium-ion battery. Background Art

[0002] Whether in the field of electric vehicles or large-scale grid energy storage, lithium-ion batteries play an irreplaceable role. Further improving the energy density and cycle life of lithium-ion batteries can deepen the electrification transformation and the construction of new power systems. Li2NiO2 is a lithium-rich transition metal oxide that can release a large amount of active lithium during the first charge and discharge process to supplement the active lithium loss caused by the SEI film, thereby effectively improving the energy density and cycle life of lithium-ion batteries.

[0003] The most suitable way to use Li2NiO2 on a large scale is to add it directly to the positive electrode slurry. This method does not require changing the existing slurry process and uses Li2NiO2 as an additive. However, Li2NiO2 has poor structural stability in humid air, and Li2O precipitates on the surface and gradually forms LiOH and Li2CO3 with moisture and CO2 in the air. The presence of LiOH and Li2CO3 easily causes the slurry to gel, making the coating process difficult. In addition, the generated LiOH and Li2CO3 have poor conductivity, which also hinders the lithium replenishment capacity of Li2NiO2 and weakens the lithium replenishment effect. In addition, Li2NiO2 forms NiO after decomposition during charging, which remains in the battery without any positive effect.

[0004] Surface coating is one of the most effective methods to improve the air stability of Li2NiO2. Researchers have modified the surface of Li2NiO2 by coating it with carbon, hydrophobic substances, oxides, fast ion conductors, etc., but these substances are all electrochemically inactive and can easily reduce the lithium replenishment capacity. Some studies have also modified the surface of Li2NiO2 by coating it with Li2Se, Li3N, Li6CoO4, etc. Although they are electrochemically active, they are still sensitive to air and moisture and cannot effectively improve the air stability of Li2NiO2.

[0005] Therefore, how to improve the air stability of Li2NiO2 through a simple and appropriate method without sacrificing its specific capacity too much is crucial for the further promotion and application of Li2NiO2.

[0006] CN115347254A discloses a composite positive electrode lithium supplement additive, including positive electrode lithium supplement material particles, characterized in that: a lithium carbonate coating layer is also combined on the surface of the positive electrode lithium supplement material particles, the lithium carbonate coating layer coats the positive electrode lithium supplement material particles, and the lithium carbonate is generated by the reaction of residual alkali contained in the positive electrode lithium supplement material particles. Although this solution realizes the coating of lithium carbonate on the lithium supplement agent to improve air stability, its lithium carbonate is only used as a coating layer and does not provide lithium supplement capacity, and the residual substances after the decomposition of the lithium-rich transition metal oxide are not used and are idle.

[0007] CN111977703A discloses a preparation method of a Li2O and Li2CO3 coated transition metal sulfide-based positive electrode material, characterized in that the preparation method comprises: adding Li2S to anhydrous ethanol in a protective atmosphere according to a required amount, stirring and mixing to obtain a clarified solution; adding transition metal sulfide-based material powder and multi-walled carbon nanotubes to the clarified solution in a required amount to form a mixed solution, and continuing to stir and heat the mixed solution until the anhydrous ethanol is completely volatilized to obtain Li2S / C coated transition metal sulfide-based material powder; grinding the obtained powder evenly, placing it in the air to stand, so that Li2S is partially or completely hydrolyzed to form LiOH; calcining the powder after standing in an inert gas, and cooling to obtain the Li2O and Li2CO3 coated transition metal sulfide-based positive electrode material. Although this scheme inhibits volume expansion, alleviates side reactions with the electrolyte and prevents the shuttling of polysulfides by coating with Li2O and Li2CO3, the capacity of Li2O and Li2CO3 as lithium supplements themselves is not fully utilized. Summary of the invention

[0008] The purpose of the present invention is to overcome the problems of poor air stability, reduced specific capacity after surface modification, and poor electrochemical performance after application in batteries of surface-modified lithium supplement agents in the prior art.

[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a coated lithium-rich lithium supplement material, which comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises Li2NiO2; the coating layer comprises a carbon-composite lithium-rich layer; the lithium-rich layer is selected from at least one of Li2CO3, Li2C2O4, and Li2C4O4;

[0010] The mass ratio of the carbon content in the Li2NiO2, the lithium-rich layer and the coating layer is 100:1-5:0.1-2.5;

[0011] The average particle diameter of the coated lithium-rich lithium supplement material is 12-18 μm.

[0012] The second aspect of the present invention provides a method for preparing the coated lithium-rich lithium supplement material according to the first aspect, the method comprising:

[0013] (1) in the presence of a solvent, mixing a lithium source and a carbon source to obtain a mixed solution;

[0014] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution;

[0015] (3) drying the precursor solution to obtain the coated lithium-rich lithium supplement material;

[0016] The lithium source is selected from at least one of Li2CO3, Li2C2O4, and Li2C4O4;

[0017] The mass ratio of the Li2NiO2, the lithium source and the carbon source is 100:1-5:0.1-2.5, calculated as Li2NiO2, the lithium source and the carbon element respectively.

[0018] The third aspect of the present invention provides a coated lithium-rich lithium supplement material prepared by the method described in the second aspect.

[0019] The fourth aspect of the present invention provides the application of the coated lithium-rich lithium supplement material described in the first aspect and the third aspect in the field of lithium-ion battery technology.

[0020] The fifth aspect of the present invention provides a lithium-ion battery, which includes: a positive electrode, a separator, and a negative electrode; the positive electrode is coated with a lithium supplement material; the lithium supplement material is the coated lithium-rich lithium supplement material described in the first aspect and the second aspect.

[0021] Compared with the prior art, the coated lithium-rich lithium supplement material provided by the present invention has the following beneficial effects:

[0022] (1) The preparation process is simple, highly reproducible, and easy to promote on a large scale;

[0023] (2) The coated lithium-rich lithium supplement material provided by the present invention has excellent air stability;

[0024] (3) The coated lithium-rich lithium supplement material provided by the present invention fully utilizes the synergistic effect of the base material and the coating layer. The base material catalyzes the coating layer to help it decompose and obtain capacity. The coating layer improves the stability of the base material, protects it from residual alkali, and enables the lithium supplement capacity to be fully utilized. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 1 is a graph showing the test results of the static contact angle of the materials obtained in Example 1 and Comparative Example 2 provided by the present invention to water;

[0026] Figure 2 It is an electron microscope image of the material obtained in Example 1 provided by way of example in the present invention. DETAILED DESCRIPTION

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] As mentioned above, the first aspect of the present invention provides a coated lithium-rich lithium supplement material, which includes a substrate and a coating layer coated on the surface of the substrate; the substrate includes Li2NiO2; the coating layer includes a carbon-composite lithium-rich layer; the lithium-rich layer is selected from at least one of Li2CO3, Li2C2O4, and Li2C4O4;

[0029] The mass ratio of the carbon content in the Li2NiO2, the lithium-rich layer and the coating layer is 100:1-5:0.1-2.5;

[0030] The average particle diameter of the coated lithium-rich lithium supplement material is 12-18 μm.

[0031] Through creative research, the present invention has found that by introducing a carbon-composite lithium-rich layer on the surface of Li2NiO2, and controlling the mass ratio of carbon elements in Li2NiO2, lithium-rich layer and coating layer within the above-mentioned specific range, the obtained coated lithium-rich lithium supplement material can simultaneously take into account excellent air stability and lithium supplement capacity; wherein, the carbon on the surface is also a hydrophobic material, which can block moisture and improve the overall conductivity, helping to play the lithium supplement capacity; the lithium-rich layer itself is also a lithium supplement, with a higher lithium supplement capacity than Li2NiO2, but it is difficult to play the lithium supplement capacity due to the high decomposition voltage, but the NiO formed by Li2NiO2 after the first cycle of charging can be used as a catalyst to effectively reduce the decomposition voltage of the lithium-rich layer, so that it can play the lithium supplement capacity. In addition, the carbon coated on the surface can also improve the conductivity of the lithium-rich layer and reduce the decomposition voltage.

[0032] In order to better utilize the lithium replenishing capacity of the coating layer, preferably, the lithium-rich layer is Li2CO3.

[0033] More preferably, the mass ratio of the carbon content in the Li2NiO2, the lithium-rich layer and the coating layer is 100: 2-5: 0.2-1. The inventors found that under this preferred embodiment, the coated lithium-rich lithium supplement agent obtained by the present invention has a higher lithium supplement capacity.

[0034] Preferably, the average particle diameter of the coated lithium-rich lithium supplement material is 12-16 μm.

[0035] As mentioned above, the second aspect of the present invention provides a method for preparing the coated lithium-rich lithium supplement material according to the first aspect, the method comprising:

[0036] (1) in the presence of a solvent, mixing a lithium source and a carbon source to obtain a mixed solution;

[0037] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution;

[0038] (3) drying the precursor solution to obtain the coated lithium-rich lithium supplement material;

[0039] The lithium source is selected from at least one of Li2CO3, Li2C2O4, and Li2C4O4;

[0040] The mass ratio of the Li2NiO2, the lithium source and the carbon source is 100:1-5:0.1-2.5, calculated as Li2NiO2, the lithium source and the carbon element respectively.

[0041] Preferably, the lithium source is Li2CO3.

[0042] More preferably, the mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:2-5:0.2-1.

[0043] Preferably, the carbon source is selected from at least one of carbon nanotubes, graphene, acetylene black and Ketjen black.

[0044] More preferably, the carbon source is selected from a carbon nanotube aqueous dispersion and / or a graphene aqueous dispersion.

[0045] Further preferably, the solid content of the carbon nanotube aqueous dispersion and the graphene aqueous dispersion is independently 4-6wt%. The present invention has found through creative research that under this preferred specific implementation, it is helpful to achieve uniform coating, and the conductivity of the obtained lithium supplement material is higher, which is also beneficial to improve the overall conductivity and reduce the decomposition voltage of the lithium-rich layer, thereby improving its lithium supplement capacity.

[0046] It should be noted that, in the present invention, if the carbon source is selected from a carbon nanotube aqueous dispersion and / or a graphene aqueous dispersion, then in the step of preparing the coated lithium-rich lithium supplement, the amount of the carbon source is calculated based on the solid content in the carbon nanotube aqueous dispersion and / or the graphene aqueous dispersion. The present invention will not be elaborated herein, and those skilled in the art should not understand it as a limitation to the present invention.

[0047] Preferably, in step (1), the mass ratio of the lithium source to the solvent is 1:100-300. The lithium ion concentration determines the solid content of the precursor solution. The present invention has found through creative research that too low a lithium ion concentration will lead to high water content, low evaporation efficiency, lengthy process, and greatly reduced energy consumption, while too high a concentration will lead to high viscosity of the precursor solution, severe agglomeration of particles after drying, which is not conducive to uniform coating. Therefore, the present invention preferably uses a lithium source to solvent mass ratio of 1:100-300.

[0048] Preferably, in step (1), the solvent is water.

[0049] Preferably, in step (1), the first mixing is performed under ultrasonic conditions, and the conditions for the first mixing include: time of 10-30 min, temperature of 25-60° C., and ultrasonic frequency of 45-55 kHz.

[0050] Preferably, in step (2), the second mixing conditions include: time of 30-120 min, temperature of 25-60°C.

[0051] More preferably, the second mixing is performed under stirring conditions. The present invention has no particular requirement on the stirring speed, and the stirring can be performed in a conventional manner in the art. For example, the stirring speed can be 1000-2000 rpm.

[0052] Preferably, in step (3), the drying is carried out by spray drying, and the conditions of the spray drying include: a feed rate of 100-2000 mL / h; and an inlet air temperature of 120-220°C.

[0053] More preferably, the spray drying conditions include: the air inlet temperature is 180-220° C. The inventors found that under this preferred embodiment, the lithium-containing solution evaporates faster, but does not cause carbon oxidation, so that the coated lithium-rich lithium supplement agent obtained by the present invention is coated more uniformly.

[0054] As mentioned above, the third aspect of the present invention provides a coated lithium-rich lithium supplement material prepared by the method described in the second aspect.

[0055] As mentioned above, the fourth aspect of the present invention provides the application of the coated lithium-rich lithium supplement material described in the first aspect and the third aspect in the field of lithium-ion battery technology.

[0056] As mentioned above, the fifth aspect of the present invention provides a lithium-ion battery, which includes: a positive electrode, a separator, and a negative electrode; the positive electrode is coated with a lithium supplement material; the lithium supplement material is the coated lithium-rich lithium supplement material described in the first aspect and the second aspect.

[0057] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, the raw materials are all commercially available.

[0058] Example 1

[0059] This example is used to illustrate that the coated lithium-rich lithium supplement material provided by the present invention is prepared by the following steps:

[0060] Carbon source: 5 wt% carbon nanotube dispersion;

[0061] Lithium source: Li2CO3;

[0062] (1) 5 g of Li2CO3 and a carbon nanotube dispersion with a concentration of 5 wt% were first mixed with 500 g of deionized water to obtain a mixed solution; the conditions of the first mixing were: an ultrasonic frequency of 50 kHz, a time of 30 min, and a temperature of 25° C.;

[0063] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 30 min, and a temperature of 25° C.;

[0064] (3) spray drying the precursor solution to obtain the coated lithium-rich lithium supplement material S1; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0065] The mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:5:1.

[0066] Example 2

[0067] Carbon source: 5 wt% carbon nanotube dispersion;

[0068] Lithium source: Li2C2O4;

[0069] (1) 5 g of Li2C2O4 and a carbon nanotube dispersion with a concentration of 5 wt% were first mixed with 500 g of deionized water to obtain a mixed solution; the conditions of the first mixing were: an ultrasonic frequency of 50 kHz, a time of 30 min, and a temperature of 25° C.;

[0070] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 30 min, and a temperature of 25° C.;

[0071] (3) spray drying the precursor solution to obtain the coated lithium-rich lithium supplement material S2; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0072] The mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:5:1.

[0073] Example 3

[0074] Carbon source: 5 wt% carbon nanotube dispersion;

[0075] Lithium source: Li2C4O4;

[0076] (1) 5 g of Li2C2O4 and a carbon nanotube dispersion with a concentration of 5 wt% were first mixed with 500 g of deionized water to obtain a mixed solution; the conditions of the first mixing were: an ultrasonic frequency of 50 kHz, a time of 30 min, and a temperature of 25° C.;

[0077] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 30 min, and a temperature of 25° C.;

[0078] (3) spray drying the precursor solution to obtain the coated lithium-rich lithium supplement material S3; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0079] The mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:5:1.

[0080] Example 4

[0081] This example is used to illustrate that the coated lithium-rich lithium supplement material provided by the present invention is prepared by the following steps:

[0082] Carbon source: 4 wt% carbon nanotube dispersion;

[0083] Lithium source: Li2CO3;

[0084] (1) 5 g of Li2CO3 and a carbon nanotube dispersion having a concentration of 4 wt% were first mixed with 500 g of deionized water to obtain a mixed solution; the conditions for the first mixing were: an ultrasonic frequency of 45 kHz, a time of 20 min, and a temperature of 25° C.;

[0085] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 120 min, and a temperature of 25° C.;

[0086] (3) spray drying the precursor solution to obtain the coated lithium-rich lithium supplement material S1; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 180° C.;

[0087] The mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:2:0.2.

[0088] Example 5

[0089] This embodiment adopts a process similar to that of Embodiment 1, except that, in this embodiment, the amount of Li2CO3 is controlled to remain unchanged, but the mass ratio of Li2NiO2, Li2CO3 and carbon source in terms of Li2NiO2, lithium source and carbon element respectively is 100:5:2.

[0090] The rest are the same as in Example 1.

[0091] The coated lithium-rich lithium supplement material S5 is prepared.

[0092] Example 6

[0093] This embodiment adopts a process similar to that of Embodiment 1, except that, in this embodiment, the amount of Li2CO3 is controlled unchanged, but the mass ratio of Li2CO3 to deionized water is 1:90 (that is, the amount of deionized water is 450g).

[0094] The rest are the same as in Example 1.

[0095] The coated lithium-rich lithium supplement material S6 was prepared.

[0096] Example 7

[0097] This example is carried out using a process similar to that of Example 1, except that in this example, a carbon nanotube dispersion having a concentration of 6.5 wt % of carbon element is used to replace the carbon nanotubes having a concentration of 5 wt % in Example 1.

[0098] The rest are the same as in Example 1.

[0099] The coated lithium-rich lithium supplement material S7 was prepared.

[0100] Example 8

[0101] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, the spray drying temperature is 150°C.

[0102] The rest are the same as in Example 1.

[0103] The coated lithium-rich lithium supplement material S8 was prepared.

[0104] Comparative Example 1

[0105] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, the amount of Li2CO3 is controlled unchanged, but the mass ratio of Li2NiO2, Li2CO3 and carbon source, calculated as Li2NiO2, lithium source and carbon element, is 100:5.5:1.

[0106] The rest are the same as in Example 1.

[0107] The material DS1 was prepared.

[0108] Comparative Example 2

[0109] This comparative example uses Li2NiO2 as a comparison.

[0110] Comparative Example 3

[0111] This comparative example is carried out using a process similar to that of Example 1, except that Li2NiO2 is not added in this comparative example. The specific preparation steps are as follows:

[0112] Carbon source: 5 wt% carbon nanotube dispersion;

[0113] Lithium source: Li2CO3;

[0114] (1) 5 g of Li2CO3 and a carbon nanotube dispersion with a concentration of 5 wt% were first mixed with 500 g of deionized water to obtain a mixed solution; the conditions of the first mixing were: an ultrasonic frequency of 50 kHz, a time of 30 min, and a temperature of 25° C.;

[0115] (2) spray drying the mixed solution to obtain the material DS3; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0116] The mass ratio of the lithium source to the carbon source, calculated as Li2NiO2, lithium source and carbon element, is 5:1.

[0117] Comparative Example 4

[0118] This comparative example is carried out using a process similar to that of Example 1, except that no carbon source is added in this comparative example. The specific preparation steps are as follows:

[0119] (1) 5 g of Li2CO3 and 500 g of deionized water were first mixed to obtain a mixed solution; the conditions of the first mixing were: ultrasonic frequency of 50 kHz, time of 30 min, and temperature of 25°C;

[0120] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 30 min, and a temperature of 25° C.;

[0121] (3) spray drying the precursor solution to obtain the material DS4; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0122] The mass ratio of the Li2NiO2 to the lithium source is 100:5.

[0123] Comparative Example 5

[0124] This comparative example is carried out using a process similar to that of Example 1, except that no lithium source is added in this comparative example. The specific preparation steps are as follows:

[0125] (1) 20 g of a carbon nanotube dispersion having a concentration of 5 wt % and 500 g of deionized water are first mixed to obtain a mixed solution; the first mixing conditions are: an ultrasonic frequency of 50 kHz, a time of 30 min, and a temperature of 25° C.;

[0126] (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; the conditions of the second mixing are: a stirring speed of 1000 rpm, a time of 30 min, and a temperature of 25° C.;

[0127] (3) spray drying the precursor solution to obtain the coated lithium-rich lithium supplement material S1; the spray drying conditions are: feed rate of 800 mL / h; inlet air temperature of 200° C.;

[0128] The mass ratio of the Li2NiO2 and the carbon source, calculated as Li2NiO2 and carbon element, is 100:1.

[0129] The parameter characteristics of the materials prepared in the above examples are shown in Table 1.

[0130] Table 1

[0131]

[0132] The present invention also provides an exemplary electron microscope image of the coated lithium-rich lithium supplement material obtained in Example 1 ( Figure 1), it can be seen from the figure that Li2NiO2 is covered by a layer of fine particles. This is because the lithium salt is dissolved in water and then spray-dried and recrystallized to form nanoparticles coated on the surface, indicating that Li2NiO2 is successfully coated by the lithium-rich layer and the carbon layer.

[0133] Test Example 1

[0134] 0.08 g of the material provided in the above example was mixed with 0.01 g of acetylene black, 0.01 g of polyvinylidene fluoride and 0.5 mL of N-methylpyrrolidone to obtain a slurry, which was coated on an aluminum foil to prepare a positive electrode sheet. The positive electrode sheet, a metal lithium sheet (negative electrode), a separator and an electrolyte were assembled into a CR2032 button battery.

[0135] The assembled battery was tested for its charge capacity in grams at a voltage range of 2.0-4.5V and a charge rate of 0.1C. The test results are shown in Table 2.

[0136] Table 2

[0137]

[0138] It can be seen from Table 2 that the coated lithium-rich lithium supplement material provided by the present invention can exert better capacity; among them, when the proportion of lithium source is high, carbon and Li2NiO2 will not be able to fully reduce their decomposition voltage, resulting in the difficulty of the lithium-rich layer to exert its capacity; but when there is no lithium-rich layer and coating layer, Li2NiO2 is easily corroded by air during the battery manufacturing process, resulting in low specific capacity; when only lithium-rich layer and carbon are contained, the specific capacity of the material is not good due to the lack of catalytic effect of Li2NiO2; when only Li2NiO2 and lithium-rich layer are contained, the specific capacity is not good due to the lack of carbon to improve the conductivity of the lithium-rich layer; when no lithium-rich layer is contained, the specific capacity of the material is not good due to the lack of capacity of the surface lithium-rich layer.

[0139] Test Example 2

[0140] This test example is used to illustrate the air stability of the coated lithium-rich lithium supplement material obtained by the present invention;

[0141] Test method: Contact angle measuring instrument. After tableting, water was used as the contact medium to measure the static contact angle by the sessile drop method. Each sample was tested 3 times. The test results are shown in Figure 2 .

[0142] from Figure 2 It can be seen that the contact angle of comparative example 2 to water is smaller, and the contact angle of example 1 to water is larger, indicating that the carbon-composite lithium-rich layer can effectively prevent Li2NiO2 from being corroded by moisture in the air.

[0143] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A coated lithium-rich lithium supplement material, characterized in that: The material comprises a substrate and a coating layer coated on the surface of the substrate; the substrate comprises Li2NiO2; the coating layer comprises a carbon-composite lithium-rich layer; the lithium-rich layer is selected from at least one of Li2CO3, Li2C2O4 and Li2C4O4; The mass ratio of the carbon content in the Li2NiO2, the lithium-rich layer and the coating layer is 100:1-5:0.1-2.5; The average particle diameter of the coated lithium-rich lithium supplement material is 12-18 μm.

2. The coated lithium-rich lithium supplement material according to claim 1, characterized in that: The lithium-rich layer is Li2CO3; And / or, the mass ratio of the carbon content in the Li2NiO2, the lithium-rich layer and the coating layer is 100:2-5:0.2-1; And / or, the average particle diameter of the coated lithium-rich lithium supplement material is 12-16 μm.

3. A method for preparing the coated lithium-rich lithium supplement material according to claim 1 or 2, characterized in that: The method includes: (1) in the presence of a solvent, mixing a lithium source and a carbon source to obtain a mixed solution; (2) performing a second mixing of Li2NiO2 and the mixed solution to obtain a precursor solution; (3) drying the precursor solution to obtain the coated lithium-rich lithium supplement material; The lithium source is selected from at least one of Li2CO3, Li2C2O4, and Li2C4O4; The mass ratio of the Li2NiO2, the lithium source and the carbon source is 100:1-5:0.1-2.5, calculated as Li2NiO2, the lithium source and the carbon element respectively.

4. The method according to claim 3, characterized in that The lithium source is Li2CO3; And / or, the mass ratio of the Li2NiO2, the lithium source and the carbon source, calculated as Li2NiO2, the lithium source and the carbon element, is 100:2-5:0.2-1.

5. The method according to claim 3 or 4, characterized in that: The carbon source is selected from at least one of carbon nanotubes, graphene, acetylene black, and Ketjen black; Preferably, the carbon source is selected from a carbon nanotube aqueous dispersion and / or a graphene aqueous dispersion; More preferably, the solid contents of the carbon nanotube aqueous dispersion and the graphene aqueous dispersion are independently 4-6 wt %.

6. The method according to any one of claims 3 to 5, characterized in that: In step (1), the mass ratio of the lithium source to the solvent is 1:100-300.

7. The method according to any one of claims 3 to 6, characterized in that: In step (1), the first mixing is performed under ultrasonic conditions, and the conditions for the first mixing include: time of 10-30 min, temperature of 25-60° C., and ultrasonic frequency of 45-55 kHz; And / or, in step (2), the second mixing conditions include: time of 30-120 min, temperature of 25-60° C.; And / or, in step (3), the drying is carried out by spray drying, and the conditions of the spray drying include: a feed rate of 100-2000 mL / h; an inlet air temperature of 120-220° C.; Preferably, the spray drying conditions include: an inlet air temperature of 180-220°C.

8. The coated lithium-rich lithium supplement material prepared by the method described in claims 3-7.

9. Application of the coated lithium-rich lithium supplement material according to claims 1, 2 and 8 in the field of lithium-ion battery technology.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises: a positive electrode sheet, a separator, and a negative electrode sheet; the positive electrode sheet is coated with a lithium supplement material; the lithium supplement material is the coated lithium-rich lithium supplement material according to claims 1, 2, and 8.

Citation Information

Patent Citations

  • Composite positive electrode lithium supplement additive and preparation method and application thereof

    CN115347254A

  • Preparation method of carbon-coated lithium-rich lithium ferrite as well as obtained product and application of carbon-coated lithium-rich lithium ferrite

    CN115642232A

  • Lithium supplement additive and preparation method and application thereof

    CN116002764A

  • Composite material as well as preparation method and application thereof

    CN117012910A

  • Modified lithium supplement agent and preparation method thereof, positive electrode composite material and lithium ion battery

    CN117954712A